Transformation and Expression of a Cloned fimA Gene in Porphyromonas gingivalis - Takahashi, Yusuke (American Society for Microbiology, 1999)
The Porphyromonas gingivalis fimbria is an important virulence factor involved in the adherence and colonization of the organism in the oral cavity. In this study, we transformed this organism with a gene, fimA(381), encoding the fimbrial subunit of P. gingivalis 381 (fimbrillin) by using the host-vector system that we developed previously and examined expression of the cloned fimA(381) gene. The recombinant plasmid pYHF2 was constructed by ligating a fragment containing the fimA(381) gene into the plasmid vector pYH420 and transformed into the restriction-deficient P. gingivalis host YH522. pYHF2 was autonomously maintained in YH522 cells, and the fimbrillin polypeptide (recombinant fimbrillin) was fully expressed. The molecular mass of the recombinant fimbrillin was evaluated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis as 41 kDa, which was identical to that of the native fimbrillin of strain 381. The amino acid sequences of the 20 amino-terminal residues of the recombinant fimbrillin and the native fimbrillin of the strain 381 were identical. In addition, characteristic long and thin fimbrial structures (recombinant fimbriae) that were distinguishable from the host’s native fimbriae when examined by immunogold electron microscopy were observed around the cell surface of the transformants containing the fimA(381) gene. These results suggested that transformation of fimA gene from a different strain of P. gingivalis followed by accumulation of the mature fimbrial subunit protein was sufficient for production of fimbrial structures that were observable by electron microscopy.